Presenting the Model of Eco-Leadership in Elementary Schools with an Interpretive Phenomenological Approach - Adel Zahed babolan; Seyyedmohammad Seyyedkalan (محیط زیست و توسعه فرابخشی)
Introduction: Nowadays, environmental protection and conservation have become a critical issue worldwide. This has led to significant managerial and leadership challenges in the current state of the educational fabric of schools. Many principals and teachers argue that talking about ecological educational and training activities and observing the environmental conditions of schools is still the missing link in the educational system, which is impossible without valid reflections and criticisms of the school environment. Thus, schools need environmental leadership to address these challenges, which has attracted the special attention of leadership researchers. This research aims to present an ecological leadership model in elementary schools with an interpretive phenomenological approach.Materials and Methods: The research method is qualitative regarding its objectives and interpretive phenomenology in data collection. The research environment consists of school principals and teachers who have a history of green schools. They were selected using a targeted snowball sampling method to reach 23 participants until theoretical saturation was achieved. The data collection tool was a semi-structured interview developed based on the understanding and experiences of teachers and school principals in different regions of Ardabil province. The interview protocol was evaluated for validity and reliability using Cohen's Kappa coefficient, which yielded a value of 0.71, indicating a relatively high level of agreement between coders.Results: The study uncovered that environmental leadership is delineated by 98 concepts across 17 axes, organized into three main themes. Drawing from insights of managers and teachers, it embodies six core attributes: fostering group cohesion, envisioning ideals, acting on beliefs, showing individual consideration, and providing inspirational motivation. These characteristics of environmental leadership are nurtured through value philosophy, goals and objectives, overarching policies, educational and training frameworks, psychological underpinnings, and sociological contexts. Nonetheless, advancing environmental leadership encounters significant challenges, necessitating a nuanced grasp of supportive environments from academic and training policymakers.     Discussion: Given the urgent need for environmental leadership in elementary schools, achieving sustainable environmental practices in the future depends on training school administrators and engaging both internal and external stakeholders. This research addresses the challenges and issues fronted by these agendas, aligning with recent Ministry of Education initiatives (since 2018) aimed at implementing environmental programs in schools. The findings of this research have innovatively defined environmental leadership within educational management, identified and analyzed environmental challenges specific to elementary schools, and proposed solutions. These insights pave the way for a new leadership model capable of navigating school ecological complexities and addressing local community environmental concerns in future crises.